2022
DOI: 10.1007/s12551-022-01029-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-Ewald methods for evaluating the electrostatic interactions of charge systems: similarity and difference

Abstract: In molecular simulations, it is essential to properly calculate the electrostatic interactions of particles in the physical system of interest. Here we consider a method called the non-Ewald method, which does not rely on the standard Ewald method with periodic boundary conditions, but instead relies on the cuto¤-based techniques. We focus on the physicochemical and mathematical conceptual aspects of the method in order to gain a deeper understanding of the simulation methodology.In particular, we take into ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 137 publications
0
9
0
Order By: Relevance
“…NVT simulations were performed at 300 K using the Bussi thermostat, while the NPT simulations additionally used the Bussi barostat under 1 bar at 300 K. The long-range electrostatics were calculated using the zero-dipole summation method, which is a cutoff-based approach utilizing a well-defined pairwise function , with the damping factor α set to 0 Å –1 and the atom-based cutoff length set to 12 Å. A time-step of 2 fs was used, with LINCS to constrain the bond lengths and SETTLE to constrain the water geometries.…”
Section: Methodsmentioning
confidence: 99%
“…NVT simulations were performed at 300 K using the Bussi thermostat, while the NPT simulations additionally used the Bussi barostat under 1 bar at 300 K. The long-range electrostatics were calculated using the zero-dipole summation method, which is a cutoff-based approach utilizing a well-defined pairwise function , with the damping factor α set to 0 Å –1 and the atom-based cutoff length set to 12 Å. A time-step of 2 fs was used, with LINCS to constrain the bond lengths and SETTLE to constrain the water geometries.…”
Section: Methodsmentioning
confidence: 99%
“…Many 'Non-Ewald' methods have been developed to calculate the electrostatic long-ranged interactions of charged systems [45] in order to speed up simulations. We now consider the method called 'pre-averaging' or 'angular-averaging' of the Ewald potential.…”
Section: Angular-averaged Ewald Potentialmentioning
confidence: 99%
“…Next, we calculate the derivative of each term in sum (45) to obtain the derivative of U 2 with respect to L:…”
Section: Appendix C Derivation Of Derivatives For U 1 and U 2 In [35]mentioning
confidence: 99%
“…It also has practical advantages such as using only O(N ) computational cost for large systems consisting of N particles 21,22 . Of course, the straight truncation cuto¤ is not used at present, due to causing signi…cant errors, but instead, the CB method with an appropriately prepared pair potential function is useful in molecular simulations [23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
“…In discussing the relationship between these methods 28 , it has been shown that they de…ne an equivalence of energies in a certain limit of some parameter value included in each method.…”
Section: Introductionmentioning
confidence: 99%